MEMAHAMI KEKERASAN PENJARA (SUATU TINJAUAN TEORITIS) - Kusumawardhani, DTP (Jurnal Masyarakat dan Budaya, 2009)
Theories of prison violence and behavior are often divided into the indigenous and importation model. This paper utilizes Irwin and Cressey’s importation model and integrates it with elements of Miller’s theory of a lower-class subculture explaining prison violence. The paper also examines other relevant theories of violent subcultures to enhance the argument that most prison violence is not indigenous to the prison but is brought to the institution as part of a pre-existing value. Keywords: Prison, Violence, Indigenous model, Importation model, Integration model